PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENILAIAN KINERJA HOTEL ( Studi Kasus Pada Grand Mahkota Hotel Pontianak) - B51106117, ANGGA PURDIKA (Jurnal KIAFE, 2013)
Research entitled Application of Balanced Scorecard For Hotel Benchmark Assessment (Case Study Grand Mahkota Hotel Pontianak) is performed in order to measure the performance of the non-financial perspective customer perspective, internal business perspective, and learning and growth perspective. To analyze and formulate performance measurement companies have done, there will be some analysis related to four perspectives in the balanced scorecard, namely: Financial perspective, analyzing financial performance based on the source of the financial statements and the balance sheets are published so that the income can be measured quantitatively.Customer perspective, analyzing how far the company's efforts to improve customer satisfaction. Internal business perspective, analyzing how the company effort to improve existing processes within the Company.Learning and growth perspective, analyzing the company's support for long-term growth and development through the conditions of expertise and skills of employees, employee satisfaction, innovation capability and employee engagement. The conclusion of this study, the overall measurement system so far using traditional systems such as measuring customer satisfaction remains. Grand Mahkota Hotel Pontianak possible to implement the Balanced Scorecard, as the Balanced Scorecard, all aspects can be measured. Application of Balanced Scorecard, is possible because of the Grand Mahkota Hotel Pontianak has formulated its vision, mission and strategy, and the results showed that the performance of the Grand Mahkota Hotel Pontianak said quite well by using the Balanced Scorecard. But the Grand Mahkota Hotel Pontianak is less capable in providing job satisfaction for employees, whereas job satisfaction will greatly affect the performance of the employees. The higher the employee's performance will certainly lead to the increasing quality of service to hotel guests. Hotel guests are satisfied by itself would be a customer who can certainly improve occupancy rates. In terms of financial, internal business, and learning has given better direction.PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENILAIAN KINERJA HOTEL ( Studi Kasus Pada Grand Mahkota Hotel Pontianak)”.